Determination of repeatability and reproducibility of the revised method for germinative capacity: Submitted on behalf of the EBC Analysis Committee - Home, S. (BrewingScience, 1998)
The method for the determination of germinative capacity of barley using hydrogen peroxide and peeling technique (EBC 3.5.2) was revised in 1995. The revised procedure has been collaboratively tested by the EBC Analysis Committee. The repeatability (r₉₅) and reproducibility (R₉₅) values were dependent upon mean values, r₉₅ = (64.23 – 0.64 m) % and R₉₅ = (51.74 – 0.50 m) %.